AGENDA PEREMPUAN DALAM GERAKAN PETANI - Solo, Tim LPTP (MUWAZAH, 2010)
Abstract: The green revolution, capitalism, neo-liberalism to corporate farming is a symbol of global forces that gave birth to unfairness for farmers especially women farmers. Even the injustice inflicted by global forces are increasingly marginalize women when in households, gender relations are constructed showing the existence of gender inequality. Therefore, the agenda must be in stretcher by the movement of women farmers should pay more attention to the unequal gender relations in the life of farmer households.